Pergeseran Nilai dan Peran Lembaga Keagamaan dalam Penanggulangan KDRT [Studi Lembaga Keagamaan di Kota Yogyakarta] - Amilia, Fatma; Mansur, Mansur; Saifuddin, Saifuddin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
Religious  institutions  looked  having  an  important  role  in responding a violence, especially for women at domestic violence. It is because  our  understanding  that  any  religion  has  never  agreed  and received any kind of violence. However, time has changed, campaign and gender  mainstreaming  has  been  actively  issued  by  the  government  and non  government  organizations.  Therefore,  the  interpretation  of  the devine  text  by  the  religious  leaders  has  also  shifted.  This  article elaborates  the  role  and  paradigm  shift  in  the  religious  institutions  in anticipating and rehabiliting domestic violence in Yogyakarta.